Transmission of Signals from Rats Receiving High Doses of Microbeam Radiation to Cage Mates: An Inter-Mammal Bystander Effect. Issue 1 (1st January 2014) - Mothersill, Carmel; Fernandez-Palomo, Cristian; Fazzari, Jennifer; Smith, Richard; Schültke, Elisabeth; Bräuer-Krisch, Elke; Laissue, Jean; Schroll, Christian; Seymour, Colin
Inter-animal signaling from irradiated to non-irradiated organisms has been demonstrated for whole body irradiated mice and also for fish. The aim of the current study was to look at radiotherapy style limited exposure to part of the body using doses relevant in preclinical therapy. High dose homogenous field irradiation and the use of irradiation in the microbeam radiation therapy mode at the European Synchrotron Radiation Facility (ESRF) at Grenoble was tested by giving high doses to the right brain hemisphere of the rat. The right and left cerebral hemispheres and the urinary bladder were later removed to determine whether abscopal effects could be produced in the animals and also whether effects occurred in cage mates housed with them. The results show strong bystander signal production in the contra-lateral brain hemisphere and weaker effects in the distant bladder of the irradiated rats. Signal strength was similar or greater in each tissue in the cage mates housed for 48hrs with the irradiated rats. Our results support the hypothesis that proximity to an irradiated animal induces signalling changes in an unirradiated partner. If similar signaling occurs between humans, the results could have implications for caregivers and hospital staff treating radiotherapy patients.